PEMBENTUKAN RELIGIUSITAS ASWAJA AL-NAHDLIYAH BAGI SANTRI DI SMP RAUDATUL ULUM 2 PUTUKREJO GONDANGLEGI MALANG - Muhammad Madarik; Hairul Puadi (LP3M IAI Al-Qolam, 2021)
The characteristics of Aswaja education are the same as the main characteristics of NU teachings, namely teachings that prioritize the principle of tawassuth (middle way), which can be complemented by i'tid?l (straight path) and taw?zun (proportional). Qualitative research method is a research method based on the philosophy of postpositivism, used to examine the condition of natural objects, (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combined), data analysis is inductive/qualitative. It is an educational institution that develops a local curriculum with religious values ??and activities, including daily habits, such as reading the letters of Jami 'as-Sharif and prayer before starting learning, praying in congregation at Zuhur, and praying Duha. Monthly activities, such as khataman al-Qur'an, tomb pilgrimage and istighosah. Raudlatul Ulum Junior High School in the Raudlatul Ulum Islamic Boarding School 2 Putukrejo Gondanglegi Malang is affiliated with the Nahdlatul Ulama (NU) organization. The development of Aswaja local content was developed at RU SMP, describing several points related to learning plans and adjusting student characteristics, school conditions, and the pesantren environment. The strengthening of Aswaja NU's local content is strengthened by the creation of an integrated learning system implementation between RU SMP and Pondok Pesantren.